Knowledge, attitude and practices of prevention of mother to child transmission of HIV(PMTCT) among women of child bearing age, in Karu Village, Abuja, Nigeria - Mamudu, Rashidat Amanosi (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.